Headache improvement after intracranial endovascular procedures in Chinese patients with unruptured intracranial aneurysm: A prospective observational study. Issue 6 (February 2017) - Zhang, Linjing; Wang, Yunxia; Zhang, Qingkui; Ge, Wei; Wu, Xiancong; Di, Hai; Wang, Jun; Cao, Xiangyu; Li, Baomin; Liu, Ruozhuo; Yu, Shengyuan
Abstract : Abstract: The aim of this study was to investigate whether there is a long-term improvement in headache of patients with unruptured intracranial aneurysms (UIAs) treated with intracranial endovascular procedures. Using a prospective design, consecutive patients with UIAs with neuroendovascular treatment from January 2014 to December 2014 were asked to participate. Headache outcomes were established before aneurysm treatment and for 6 months following treatment. Factors associated with different headache outcomes were investigated. Ultimately, 58 patients completed the 6-month follow-up. In total, 29 patients had preoperative headache. Six months after the intracranial endovascular procedure, 13 patients (44.8%) stated that their headaches were relieved after endovascular treatment; headache in 1 patient improved slightly, and 12 reported disappearance of headache and marked improvement. Overall, the mean headache scores of 29 patients improved on the self-reported Numeric Rating Scale (NRS) after endovascular treatment (6.00 vs. 2.30; P  < 0.001). Patients with pretreatment tension-type headache, more severe headaches, stent-assisted coiling, and stent implantation of the aneurysm were the important disadvantage for patients in improvement of post-procedure headache. Treatment of UIAs resulted in relief of headaches in about half of patients who had headaches pre-operatively.